Analysis of Sustainable Development of SMEs and Factors Influencing to the Ecotourism Industry - TUREKULOVA, Dametken; BEISENGALIYEV, Berik; VALIYEVA, Saltanat; KURMANKULOVA, Nurzhamal; SAIMAGAMBETOVA, Gaukhar (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).19, 2022)
In order for companies, regardless of scale, to survive, function normally and have prospects for development in the current dynamic, competitive and business environment, partner search, outsourcing and participation of SMEs in the supply chains of multinational corporations are necessary. This is important because the process of globalization, integration, liberalization of markets has led to great business opportunities for SMEs, where financial sustainability matters.